Experimental Study on Heat Transfer and Friction Factor in Laminar Forced Convection over Flat Tube in Channel Flow - Tahseen, Tahseen Ahmad; M. M., Rahman; M., Ishak (Elsevier Ltd, 2015)
The heat transfer and fluid flow over a flat tube in the channel with laminar forced convection is experimentally investigated. The experiments were conducted at a flat tube in the flow direction, the five air velocity between 0.2 and1.0 m/s, and Reynolds number based on the hydraulic diameter (ReDh) was considered from 124.5 to 622.5. The uniform heat flux supplies are at the surface of the tube are 354.9, 1016.3 and 1935.8 W/m2 respectively. The experimental results indicate that the average Nusselt numbers View the MathML source for the flat tube increased with increase of ReDh at fixed of the heat flux supply. The View the MathML source increased with an increase of heat flux supply at fixed ReDh. On the other hand, the friction factor decreased with increases of the front free stream velocity. The View the MathML source relationship with ReDh in the power law, theView the MathML source–ReDh correlation was found to be View the MathML source. The correlation achieved good predictions of the measured data with the minimum root mean square value is 99.70%.